The Effect of Reciprocal Teaching Assisted by Wordwall Media on Students’ Mathematical Communication and Resilience - Deasya, Reisha Alifia; Maratusholihah, Istiadzah; Laelasari, L; Nasir, Fuad (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to analyze the differences in students' mathematical communication and resilience skills between conventional learning and reciprocal teaching assisted by Wordwall. The study was conducted due to the limited research combining the reciprocal teaching method with interactive media to improve students' communication skills and resilience. The research population consist of eighth-grade students at a junior high school in Cirebon Regency, with samples taken using purposive sampling. The samples taken from classes VIII B and E, totaling 65 students. Using a quantitative approach with a pretest-posttest control group design and instruments in the form of tests and questionnaires, the results showed that the average posttest score for mathematical communication in the experimental class was 75.27, higher than the control class, which was 31.25. Conversely, the posttest score for mathematical resilience in the control class was 81.50, higher than that of the experimental class, which was 74.03. These findings indicate that the integration of reciprocal teaching and Wordwall has the potential to improve students' mathematical communication, although further research is needed to identify effective strategies for maintaining students' resilience.